Entre muros: as expectativas e aspirações educacionais em torno de adolescentes em conflito com a lei cumprindo a medida socioeducativa de internação em Minas Gerais - Zakia Ismail Hachem (2012)
The present study attempts to capture the educational aspirations of adolescents in conflict with the law as fulfilling socio-educational intern in Minas Gerais and the expectations of professionals in the socio-educationals centers around these adolescents. The sociological concepts on the theme aspirations and expectations" were discussed, as well as the discussion about the totalizing nature of socio-educational centers. The legal framework involving inmates in detention centers was raised, as well as previous studies that addressed this public schooling. Considering the theory and legal studies, in-depth interviews collected by a survey developed by the João Pinheiro Foundation in 2009 were analyzed, trying to articulate theory and practice on the proposed problem. In general, the analysis of the interviews showed that the expectations of the entire team of professionals are strongly associated with the trajectory of past life of the inmates, marked by poverty, high school dropout and age-grade gap. This finding is consistent with the findings of Sewell, Haller and Ohrlendorf (1970), who found in his diagram great influence of socioeconomic status in the individual to the expectations of other significant around them, with direct consequences on their academic performance. The interviews showed that the past of a teenager has great influence on the projection that center professionals make about the future of them. As a final result, it was realized that the biggest obstacle to the materialization of the educational aspirations of adolescents is outside the walls.